RELATIONSHIP BETWEEN GREEN MANAGEMENT AND GREEN HUMAN RESOURCE MANAGEMENT IN PROMOTING ECO-SUSTAINABLE VALUES- A TRANSACTIONAL ANALYSIS PERSPECTIVE - Mishra, Rajita; Saha, Jhuma (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study attempted to understand the relationship between Green Management, Green HRM and their role in promoting eco-sustainable values in individuals working in Public Sector organizations. For the study individuals working in several Public sector organizations located in Raipur, CG, were approached and their responses were recorded. Results from the study indicated significant relationship between green human resource management and individual eco-sustainable values. Similarly, the responses also indicated significant relationship between green management and individual eco- sustainable values. Importantly, the study also reported significant moderation of green management on the relationship between green human resource management and individual green values. The study forwards implication for organizations followed by limitations and scope for future studies.